1990
DOI: 10.1123/apaq.7.3.249
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Concurrent Validity of the Test of Motor Impairment-Henderson Revision

Abstract: The reliability and concurrent validity of the Test of Motor Impairment-Henderson Revision was evaluated employing a sample of preschoolers. Absolute reliability of the final test score was established by calculating the standard error of measurement (SEM). An SEM of .86 was obtained. The consistency of decisions related to motor impairment or nonimpairment was estimated by calculating the proportion of agreement index across two testing occasions and Kappa. A 90% agreement was obtained with Kappa equal to .71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
11
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…Although the M‐ABC has been compared against the full BOTMP before (Riggen et al . 1990; Henderson & Sugden 1992), this is the first study to compare a lay‐administered short form version of the BOTMP to a clinician‐administered M‐ABC.…”
Section: Discussionmentioning
confidence: 99%
“…Although the M‐ABC has been compared against the full BOTMP before (Riggen et al . 1990; Henderson & Sugden 1992), this is the first study to compare a lay‐administered short form version of the BOTMP to a clinician‐administered M‐ABC.…”
Section: Discussionmentioning
confidence: 99%
“…However, the selection of stricter cut-off scores in previous studies has also led to poor accuracy in identifying these children. 9,10,14 A limitation of the current study was that the sample did not include any child who had been previously identified as having motor problems; therefore, no comparison of test results with functional performance could be attained.…”
Section: Discussionmentioning
confidence: 99%
“…The SF was found to be a valid test of motor proficiency in Greek preschool and primary school children without disabilities. 8 Regarding the discriminative accuracy of the SF, findings of previous studies 9,10 have shown that there is a remarkable inconsistency between classification of motor impairment (MI) on the BOTMP-SF compared with other tests such as the McCarron Assessment of Neuromuscular Development 11 and the Test of Motor Impairment -Henderson revision. 12 Both of the aforementioned tests were found to be more accurate discriminators of MI than the SF.…”
mentioning
confidence: 99%
“…One of the gold-standards for motor development is the Bruininks-Oseretsky Test of Motor Proficiency (Hattie & Edwards, 1987; Riggen, Ulrich, & Ozmun, 1990; Tan, 2001). This is a standardized and norm-referenced test of motor development that is widely used by clinicians (especially occupational and physical therapists) and researchers to evaluate motor performance and to discriminate children with motor disorders from those who are developing normally.…”
mentioning
confidence: 99%